1990
DOI: 10.1039/ft9908604001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reactions of CH3O and CD3O with NO

Abstract: The kinetics of the reactions of CH, O and CD30 with NO have been studied using a discharge flow reactor. CH, O and CD30 were detected using laser-excited fluorescence (LEF) near 300 nm. Total rate coefficients for the reaction of CH, O with NO were measured as a function of temperature (220-473 K) and pressure (0.755.0 Torr) of He or Ar. Total rate coefficients for the CD30 + NO reaction were measured at ca. 294 K over the pressure range 0.75-5.0 Torr He. Using molecular-beam mass spectrometry, the CH30N0 yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
5
14
1
Order By: Relevance
“…The reaction with NO follows either a disproportionation pathway to HNO + CH 2 O (R4) or an association path to CH 3 ONO (R5). The preferred rate expressions are taken from the study by Caralp et al [84], who interpreted their own measurements of the overall rate of NO + CH 3 O and data from the literature [85][86][87][88] in terms of a multichannel RRKM analysis. The potential energy surface calculations indicated that the disproportionation reaction (R4) occurs simultaneously by direct Habstraction at the nitrogen atom of NO and by formation of the adduct CH 3 ONO * followed by rearrangement and bond cleavage to HNO + CH 2 O.…”
Section: No X /Alkoxy Reactionsmentioning
confidence: 99%
“…The reaction with NO follows either a disproportionation pathway to HNO + CH 2 O (R4) or an association path to CH 3 ONO (R5). The preferred rate expressions are taken from the study by Caralp et al [84], who interpreted their own measurements of the overall rate of NO + CH 3 O and data from the literature [85][86][87][88] in terms of a multichannel RRKM analysis. The potential energy surface calculations indicated that the disproportionation reaction (R4) occurs simultaneously by direct Habstraction at the nitrogen atom of NO and by formation of the adduct CH 3 ONO * followed by rearrangement and bond cleavage to HNO + CH 2 O.…”
Section: No X /Alkoxy Reactionsmentioning
confidence: 99%
“…The reaction with NO follows either a disproportionation pathway to HNO + CH 2 O (R76) or an association path to CH 3 ONO (R77). The preferred rate expressions are taken from the study by Caralp et al 140 who interpreted their own measurements of the overall rate of NO + CH 3 O and data from the literature 141–144 in terms of a multichannel RRKM analysis. The potential energy surface calculations indicated that the disproportionation reaction (R76) occurs simultaneously by direct H‐abstraction at the nitrogen atom of NO, and by formation of the adduct CH 3 ONO* followed by rearrangement and bond cleavage to HNO + CH 2 O.…”
Section: Chemical Kinetic Modelmentioning
confidence: 99%
“…The reaction between the most simple alkoxy radical, CH 3 O, and NO has been the subject of many studies either on the rate constant [10,11,12,16] or on the product yields [13,14,15]. It is now admitted [10], that this reaction occurs via two different pathways: a disproportionation channel (dominating at low pressures) and an addition channel (becoming more important at higher pressures):…”
Section: The Reaction Of Alkoxy Radicals With Nomentioning
confidence: 99%